Analisa Profitabilitas, Likuiditas, Dan Solvabilitas Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Pada Masa Sebelum Dan Saat Pandemi Covid-19 - Pramandyah Fitah Kusuma; Endah Supeni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to analyze and compare the Profitability, Liquidity, and Solvency Ratios, in Property and Real Estate Companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 Pandemic. The data used in this study used data before the pandemic. covid is in 2019 and when the covid pandemic is still ongoing, namely 2020 with the object of research being Property and Real Estate companies listed on the Indonesia Stock Exchange with a total sample of 30 companies. The research method uses the Quantitative Method in tabulated form through testing using SPSS 20. The results show that there are differences in the profitability of property and real estate companies before the COVID-19 pandemic and during the COVID-19 pandemic. The liquidity of property and real estate companies has no difference before. the covid 19 pandemic and during the covid 19 pandemic. The solvency of property and real estate companies is different before the covid 19 pandemic and during the covid 19 pandemicKeywords: Profitability, Liquidity, Solvency, Covid-19 Pandemic